Pregnancy after Age 50: Defining Risks for Mother and Child - Kort, Daniel H.; Gosselin, Jennifer; Choi, Janet M.; Thornton, Melvin H.; Cleary-Goldman, Jane; Sauer, Mark V. (American Journal of Perinatology, 2012)
Assisted reproductive technology using donor-egg in vitro fertilization (D-IVF) has enabled women 50 years and above to successfully achieve pregnancy. We examine the safety profile of these pregnancies through a large, single-center case series and retrospective cohort analysis in which all participants were carefully screened medically prior to conception. Consecutive women aged ≥ 50 years (n = 101) who achieved a viable pregnancy via D-IVF were identified and their perinatal outcomes were recorded. These data were compared with control data from younger (≤ 42 years) recipients of D-IVF (n = 41) who also achieved a viable pregnancy at our center during the same period. Compared with the younger women, older recipients had statistically similar rates of hypertensive disorders of pregnancy (23% versus 14%, odds ratio [OR] 1.9 [0.65 to 5.4]), gestational diabetes (4.0% versus 3.0%, OR 1.4 [0.15 to 113.0]), preterm premature rupture of membranes/preterm labor (8.9% versus 14%, OR 0.59 [0.18 to 1.9]), and abnormal placentation (2.1% versus 0%). Cesarean delivery was high in women ≥ 50 (81% of singletons, 100% of multiples). There was one maternal death, which occurred before delivery in a 49-year-old woman who would have been 50 at term had she survived, presumably secondary to myocardial infarction. Primary neonatal outcomes of gestational age and birth weight were excellent and similar between groups. Women ≥ 50 years who achieve pregnancy via D-IVF are at high risk for maternal complications, particularly hypertensive disorders and cesarean section, but at rates similar to those seen in younger recipients.
Keywords: menopausal pregnancy; egg donation; IVF